(untitled) (International Journal of Studies in Nursing, 2019)
Background Health care professionals find themselves participating in insignificant events in human existence such as birth, pain, and death which is a privilege but also poses challenges as this participation involves decisions that can be life-changing and having an effect on everyone involved. The study aimed to explore moral distress within the context of Saudi Arabia. Methodology A simple qualitative design was used with a research paradigm of constructivism. Data collection included in-depth interviews with five critical care nurses who were purposively sampled. The setting for the study was the critical care units at King Abdul- Aziz Medical City- Jeddah. Data analysis included content analysis. Principles of academic rigor were followed. Findings Two themes emerged from this study with various subthemes. Theme 1: Turning away from nursing obligations: hands are tied, the burden of workload, no voice, not honoring oath; Theme 2: Bad practice: hierarchy in practice and feeling guilty. Conclusions This study highlights that moral distress within critical care units is a real problem that impacts on critical care nurses’ physical and psychological stress. Health care institutions should mobilize resources to reduce these effects on critical care nurses and other health care professionals.